Fluorinated Cycloalkyl Building Blocks for Drug Discovery. (5th October 2022) - Grygorenko, Oleksandr O.; Melnykov, Kostiantyn P.; Holovach, Serhii; Demchuk, Oleksandr
Abstract: The review covers various aspects of fluorinated cycloalkyl (C3 −C7 ) building blocks for drug discovery, including their synthesis, key physicochemical properties, and biological and medicinal applications of their derivatives. The discussed synthetic methods include classical nucleophilic fluorinations of various substrates, the addition of fluorine and another heteroatom to double bonds, cycloadditions and other transformations of fluorine‐containing substrates, as well as some newer reactions like fluorination of non‐activated and remotely activated C−H bonds, decarboxylative and deborylative fluorinations, etc. The known data on the effect of introducing the fluorinated cycloalkyl groups on the compound's key in vitro parameters (such as acidity/basicity, lipophilicity, conformational behavior, and short contact capabilities) are surveyed. Finally, applications of fluorinated cycloalkyl building block derivatives in the design of biologically active compounds (including marketed drugs Maraviroc, Ivosidenib, and Sitafloxacin) are covered, with a focus on the fluorination impact. Abstract : This review article surveys synthetic approaches towards fluorinated cycloalkyl building blocks for drug discovery, their key physicochemical properties, and applications in medicinal chemistry. Examples of successful biologically active derivatives (including marketed drugs) are given, with focus on the role of the fluorinated cycloalkyl substituent in their design.